Städtediplomatie in den 2020er Jahren: Mehr als eine Geschichte zweier Städte. Kommunale Diplomatie und Städtepartnerschaften zwischen Deutschland, Europa und China. Implikationen für Nordrhein-Westfalen; Urban diplomacy in the 2020s: More than a tale of two cities. City diplomacy and municipal partnerships between Germany, Europe and China. Implications for North Rhine-Westphalia - Thomas Heberer; Anna Shpakovskaya (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2022)
– This policy paper contributes to the topic of German-Chinese municipal partnerships, with a focus on the state of North Rhine-Westphalia (NRW). It first builds a bridge between the idea of town twinning and the future-oriented thematic complex of city diplomacy. Secondly, it looks at the connection between German-Chinese city partnerships and the topic of city diplomacy and deals with the change in the idea of partnership. Thirdly, it discusses the German-Chinese municipal partnerships in NRW, including school partnerships as part and parcel of citizens' exchange. Section 4 briefly looks at the first Sino-German twinning between Duisburg and Wuhan, which celebrated its 40th anniversary in 2022. Part 5 looks at the role of town twinning as an economic and cultural factor, and Part 6 at the question of current fields and contents of such partnerships. Section 7 deals with the challenges of German-Chinese municipal partnerships with regard to critical or "sensitive" issues, Part 8 with the current "China image" in Germany and the criticism of sub-national diplomacy concerning German-Chinese partnerships, before Point 9 draws a general conclusion.
Keywords: 330; municipal partnerships; urban diplomacy; school partnerships; subnational diplomacy; Duisburg; AreaRuhr; North Rhine-Westphalia; German-China relations